Design of stainless steel continuous beams with tubular cross-sections. (15th November 2017) - Arrayago, I.; Real, E.; Mirambell, E.
Highlights: The applicability of global plastic design for stainless steel continuous beams is investigated. Existing Class 1 limits are statistically assessed. The CSM approach for indeterminate structures is also evaluated. New DSM-based approach is proposed for stainless steel continuous beams. Plastic design approaches including strain hardening provide best capacity predictions. Abstract: This paper presents a comprehensive study on the application of global plastic design methods, not currently allowed in European specification provisions, to stainless steel rectangular and square hollow section continuous beams. The analysis of experimental and numerical continuous beam strengths highlighted that ultimate capacity predictions calculated based on global elastic analysis result in a considerable conservatism due to strain hardening and bending moment redistribution effects. Alternatively, the assessment and reliability analyses of the traditional plastic design methods demonstrated that the Class 1 cross-section limit provided in the European specification can be safely applied for the partial safety factor γM0 currently provided. However, the analysis evidenced that including bending moment redistribution in capacity predictions is not enough since strain hardening effects play an important role when stocky cross-sections are analysed. Thus, the Continuous Strength Method for indeterminate structures was also assessed and it was found to provide accurate capacity predictions for all analysed stainless steel grades. Finally, an alternative Direct Strength Method design approach is proposed for stainless steel continuous beams based on the Direct Strength Method bending capacity. The proposed method, statistically validated, accounts for strain hardening effects and moment redistribution and provides the best resistance predictions among the different design methods considered.